The Developing Beginning Reading Comprehension Using Pictured Story Media For First Grade Elementary School Students - Ulfa, Maria (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Online learning makes it difficult for first-grade teachers to carry out learning on preliminary reading material. Beginning reading is the most important stage for students to be able to follow the learning at the next stage. The purpose of this study was to describe the improvement of students' initial reading skills using picture story media. The research method used in this study is classroom action research with 3 cycles. The subjects in this study were the first graders of SD Negeri Bojong Nangka 01 for the 2020/2021 academic year. The data in this study were obtained from observations, interviews, and tests. The validity of the data using triangulation techniques and sources. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results showed that using illustrated story media could improve the reading skills of first graders at SD Negeri Bojong Nangka 01 for the 2020/2021 Academic Year. In the third cycle, the average score of students was 76.67 with a complete score of 83.88%. In the implementation of early reading learning using illustrated story media, parents should accompany students in order to achieve learning objectives